The Application of the ‘Buzz’ Method in the Melayu Islam Beraja Subject - Arifah Aqilah Janudin; Abu Bakar Madin (Al-Insan: Islamic and Humanities Perspectives Journal, 2025)
The national education system in the current century necessitates teaching and learning processes that emphasise a student-centred approach within classroom settings. However, a proportion of students continue to demonstrate weaknesses in expressing their opinions and responding to questions posed during lessons. Through the application of the Buzz Method in the Melayu Islam Beraja (MIB) subject, the researcher seeks to examine the effectiveness of this strategy in facilitating more active student participation in sharing ideas and enhancing academic achievement. The challenges faced by students in articulating their views and their passive behaviour in responding to questions prompted the researcher to implement this method in classroom practice. The Buzz Method enables students to initiate small-group discussions prior to presenting responses, thereby building their confidence to speak and answer questions. Consequently, the research objectives and research questions were successfully addressed. Findings obtained through interview instruments and pre- and post-tests, analysed thematically and using the Wilcoxon Signed Ranks test, demonstrated positive outcomes, with a p-value of 0.000 < 0.05. This indicates a statistically significant difference, confirming that the application of the Buzz Method effectively improves student performance.